ANALISA SIKLIS VOLTAMETRI SUPERKAPASITOR MENGGUNAKAN ELEKTRODA KARBON AKTIF DARI KAYU KARET BERDASARKAN VARIASI AKTIVATOR KOH - E. Taer; Zulkifli Zulkifli; Sugianto Sugianto; R. Syech; R. Taslim (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Has successfully analyzed the carbon electrode supercapacitor from rubber wood using cyclic voltammetry method. Making the samples of early stage through the process of cutting, drying, carbonization and polishing to form pellets. Variations activator KOH and HNO3 is used to increase the surface area of ​​the electrode. Variations KOH used was 1 M, 3 M, 5 M HNO3 solution while being used is 25%. Methods of measurement of cyclic voltammetry carried out using a Solatron 1280 with a potential window of 0 to 1 Volt at the scan rate variation 1 mV/s, 5 mV/s, 10 mV/s, 30 mV/s, 50 mV/s and 100 mV/s. From data analized has found that the highest specific capacitance values ​​occur at the rate of induced 1 mV/s for all variations of KOH. The highest specific capacitance value at scan rate 1 mV/s in the variation of KOH 1 M, 3 M, 5 M is at 16,36 F /gram, 68,27 F/gram and 63,24 F/gram. Additional testing was also performed using X-ray diffraction instrument and electron scanning microscope. Keywords : Cyclic Voltammetry, Supercapacitor, Carbon Electrode, Rubber Wood.